Lifestyle and demographic correlates of poor mental health in early adolescence - Robinson, M.; Kendall, Garth; Jacoby, P.; Hands, B.; Beilin, L.; Silburn, Sven; Zubrick, Stephen; Oddy, W. (Blackwell Scientific Publications, 2011)
Lifestyle and demographic correlates of poor mental health in early adolescence 1. Monique Robinson1,2, 2. Garth E Kendall4, 3. Peter Jacoby1, 4. Beth Hands6, 5. Lawrie J Beilin3, 6. Sven R Silburn5, 7. Stephen R Zubrick5, 8. Wendy H Oddy1,*Article first published online: 26 OCT 2010DOI: 10.1111/j.1440-1754.2010.01891.x© 2010 The Authors. Journal of Paediatrics and Child Health © 2010 Paediatrics and Child Health Division (Royal Australasian College of Physicians)IssueJournal of Paediatrics and Child HealthJournal of Paediatrics and Child HealthVolume 47, Issue 1-2, pages 54–61, January/February 2011Additional Information(Show All)How to CiteAuthor InformationPublication HistoryHow to CiteRobinson, M., Kendall, G. E., Jacoby, P., Hands, B., Beilin, L. J., Silburn, S. R., Zubrick, S. R. and Oddy, W. H. (2011), Lifestyle and demographic correlates of poor mental health in early adolescence. Journal of Paediatrics and Child Health, 47: 54–61. doi: 10.1111/j.1440-1754.2010.01891.xAuthor Information 1. 1 Telethon Institute for Child Health Research, Centre for Child Health Research and Schools of 2. 2 Psychology 3. 3 Medicine and Pharmacology, The University of Western Australia, Royal Perth Hospital and Western Australian Institute for Medical Research 4. 4 School of Nursing and Midwifery 5. 5 Curtin Health Innovation Research Institute, Centre for Developmental Health, Curtin University of Technology, Perth 6. 6 University of Notre Dame, Fremantle, Western Australia, Australia*Correspondence: Wendy H Oddy,*Correspondence: Associate Professor Wendy H Oddy, Telethon Institute for Child Health Research, PO Box 855, West Perth, WA 6872 Australia. Fax: +61 8 9489 7700; email: wendyo@ichr.uwa.edu.auPublication History 1. Issue published online: 23 JAN 2011 2. Article first published online: 26 OCT 2010 3. Accepted for publication 29 March 2010.SEARCHSearch ScopeSearch String * Advanced > * Saved Searches >SEARCH BY CITATIONVolume:Issue:Page:ARTICLE TOOLS * Get PDF (326K) * Save to My Profile * E-mail Link to this Article * Export Citation for this Article * Get Citation Alerts * Request Permissions * Abstract * Article * References * Cited ByView Full Article (HTML) Get PDF (326K)Keywords: * adolescent; * life style; * mental health; * nutrition; * Raine StudyAim: To determine the constellation of lifestyle and demographic factors that are associated with poor mental health in an adolescent population.Methods: The Raine Study 14-year follow-up involved primary care givers and their adolescent children (n= 1860). The Child Behaviour Checklist (CBCL) was used to assess adolescent mental health. We examined diet, socio-demographic data, family functioning, physical activity, screen use and risk-taking behaviours with mental health outcomes using linear regression.Results: Adolescents with higher intakes of meat and meat alternatives and ‘extras’ foods had poorer mental health status. Adverse socio-economic conditions, higher hours of screen use and ever partaking in the health risk behaviours of smoking and early sexual activity were significantly associated with increasing CBCL scores, indicative of poorer functioning.Conclusions: By identifying the lifestyle and demographic factors that accompany poorer mental health in early adolescence, we are able to better understand the context of mental health problems as they occur within an adolescent population.